Spruce quality in mixed stands - Witkowska, Izabela (SLU/Southern Swedish Forest Research Centre, 2008)
Due to changes in Swedish forestry there is an increasing interest in growing mixed stands. Earlier studies indicate that shelterwood systems combined with dense natural regeneration of spruce resulted in reduced branchiness and improved graded quality of spruce. The study aims at answering the question: what could be the benefit of growing mixed stands with spruce in regard of the wood quality? The thesis is divided into two parts: a literature review and research based on the field data. The second part is a field study examining quality traits of spruce trees growing in different types of mixed stands. The first type represents "nurse trees" (shelter) where spruce is mixed with a fast growing species. The second type is spruce planted with noble tree species, which is designated as a final crop (e.g. beech). The following properties were measured on sample trees: breast height diameter, height, height to the first living branch, the number of branches per 1 meter of stem, the diameter of the thickest branch, stem crookedness, quality, tree class, vitality, occurrence of spike knots and double top. The significance calculations were made as planned comparisons (contrasts) in ANOVA. Every row was regarded as an independent variable. Contrasts were made between "control" (spruce stands) and the two other categories, which represented two models of competition within the stands, namely: sheltered spruce (spruce- hybrid aspen, spruce- birch and spruce- larch) and dominating spruce (with beech). The general trend was that spruce in pure stands and in mixture with beech was on average higher and had bigger diameter than spruce under shelter wood conditions. The frequency of dominant trees was also bigger in this group. The quality properties (branch properties, stem defects, vitality) indicated that superior timber quality was obtained in monocultures.